Perencanaan Program Penyuluhan Perikanan di Desa Anturan, Buleleng, Bali - Siti Aminah (Buletin Ekonomi Perikanan, 2003)
Program planning Is a crucial thing to be designed in order to provide a basic foundation for running an activity and to assess the progress of the job. A well designed program planning will play an Important role In providing a framework to the Implementation stage of the program. Extension as a non formal education conducted In the fisheries communities has an objective to help people to help themselves In terms of Improvement of the quality of life including better livelihoods, better business and better social environment. To achieve this objective, It Is clear that a strategic planning for the Improvement community should be established. People work with the community, such as extension workers, lecturers, researchers, trainers and non govermental organisation should have a holistic view about how should a program planning be constructed to face and to solve the complex Issue of fisheries community development.